2017
DOI: 10.21273/hortsci11570-16
|View full text |Cite
|
Sign up to set email alerts
|

Camellia as an Oilseed Crop

Abstract: Camellia is one of the four main oil-bearing trees along with olive, palm, and coconut in the world. Known as “Eastern Olive Oil,” camellia oil shares similar chemical composition with olive oil, with high amounts of oleic acid and linoleic acid and low saturated fats. Camellia was first exploited for edible oil in China more than 1000 years ago. Today, its oil serves as the main cooking oil in China’s southern provinces. Introduction of camellia oil into the Western countries was delayed until the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…ALA has been linked to a variety of health benefits, including reduced blood pressure, inhibition of platelet aggregation, and a lower risk of cancer 9,10 . The UFA content of tree peony seed oil complies with the international nutritional standards for “omega meals” and is similar to oil from olive and camellia trees, which are two of the world’s main oil-producing trees 11,12 . Tree peony seeds are also rich in polysaccharides, amino acids, and flavonoids 13,14 .…”
Section: Introductionmentioning
confidence: 53%
“…ALA has been linked to a variety of health benefits, including reduced blood pressure, inhibition of platelet aggregation, and a lower risk of cancer 9,10 . The UFA content of tree peony seed oil complies with the international nutritional standards for “omega meals” and is similar to oil from olive and camellia trees, which are two of the world’s main oil-producing trees 11,12 . Tree peony seeds are also rich in polysaccharides, amino acids, and flavonoids 13,14 .…”
Section: Introductionmentioning
confidence: 53%
“…Camellia oleifera ( Camellia oleifera Abel . ), which belongs to Theaceae , is an endemic woody edible oil tree species in China, and it is also one of the four major woody oil crops in the world (Liang et al., 2017). Camellia seed oil (CSO) is a vegetable oil extracted from camellia seeds, which fatty acid composition and physical and chemical properties are very similar to olive oil, so it is known as “Oriental Olive Oil” (Zhu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…
Camellia oleifera (Camellia oleifera Abel. ), which belongs to Theaceae, is an endemic woody edible oil tree species in China, and it is also one of the four major woody oil crops in the world (Liang et al, 2017). Camellia seed oil (CSO) is a vegetable oil extracted from camellia seeds, which fatty acid composition and physical and chemical properties are very similar to olive oil, so it is known as "Oriental Olive Oil" (Zhu et al, 2020).It is rich in monounsaturated fatty acids and a variety of functional active ingredients, such as squalene, phytosterols (β-sitosterol, rapeseed sterol, and stigmasterol), polyphenols, fat-soluble vitamins (vitamins A, B, E), and so on, which has high nutritional value and health-care function (Shi et al, 2020).
…”
mentioning
confidence: 99%
“…It has been reported that the planting area of C . oleifera in China exceeds 65 million acres [12]. Camellia oil, the product of C .…”
Section: Introductionmentioning
confidence: 99%